Compressible analysis of Bénard Convection of magneto rotatory couple-stress fluid - Mehta, C.B.; Singh, M. (Zielona Góra: Uniwersytet Zielonogórski)
Thermal Instability (Benard`s Convection) in the presence of uniform rotation and uniform magnetic field (separately) is studied. Using the linearized stability theory and normal mode analyses the dispersion relation is obtained in each case. In the case of rotatory Benard`s stationary convection compressibility and rotation postpone the onset of convection whereas the couple-stress have duel character onset of convection depending on rotation parameter.
Keywords: couple-stress fluid; compressibility; rotation; magnetic field and thermal convection